2021
DOI: 10.1002/ccd.29711
|View full text |Cite
|
Sign up to set email alerts
|

Association of acute kidney injury with outcomes in patients undergoing percutaneous left atrial appendage closure

Abstract: Objectives: Using a large nationally representative database, we aimed to examine risk factors for acute kidney injury (AKI) and its association with outcomes in patients undergoing percutaneous left atrial appendage closure (LAAC).Background: Previous small-scale studies have reported poor outcomes with AKI following percutaneous LAAC. Methods:We queried the Nationwide Readmission Database to identify LAAC procedures performed from 2016 to 2017. Multivariable logistic and linear regression models were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…Patients referred for LAAO are usually elderly and have a high (15%-25%) prevalence of chronic renal insufficiency. 17 , 78 , 79 , 80 Hence, these patients are at risk of developing acute kidney injury (AKI) after the procedure, which has been shown to carry major negative prognostic implications. In 1 study, the incidence of AKI after LAAO was 9%, and this was associated with a 2.5-fold increase in all-cause mortality at 18 months.…”
Section: Procedural Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients referred for LAAO are usually elderly and have a high (15%-25%) prevalence of chronic renal insufficiency. 17 , 78 , 79 , 80 Hence, these patients are at risk of developing acute kidney injury (AKI) after the procedure, which has been shown to carry major negative prognostic implications. In 1 study, the incidence of AKI after LAAO was 9%, and this was associated with a 2.5-fold increase in all-cause mortality at 18 months.…”
Section: Procedural Optimizationmentioning
confidence: 99%
“… 80 In another study, AKI after LAAO was associated with a 60% higher readmission rate at 6 months. 79 Hence, efforts have been made to optimize iodine contrast usage in the procedure to mitigate the risk of AKI. Proof-of-concept studies have shown the utility of contrast-free LAAO aided by 3D TEE, ICE, or 3D ultrasound mapping ( Figure 12 ).…”
Section: Procedural Optimizationmentioning
confidence: 99%
“…To see the LAA before and after closure during LAAC, contrast is routinely used. Approximately 10% to 13% of patients undergoing LAAC have reported AKI [29][30][31]. AKI after LAAC has previously been reported to be independently correlated with CKD [31].…”
Section: Discussionmentioning
confidence: 99%
“…laikotarpiu. Siekiant sumažinti ŪIFN riziką, buvo stengiamasi optimizuoti jodo kontrasto naudojimą procedūros metu [35]. Pasitelkiant 3D TEE, IKE arba 3D ultragarsinį kartografavimą, galima procedūrą atlikti be kontrasto.…”
unclassified